1999
DOI: 10.1016/s0741-5214(99)70239-9
|View full text |Cite
|
Sign up to set email alerts
|

New duplex ultrasound scan criteria for managing symptomatic 50% or greater carotid stenosis

Abstract: These redefined criteria detect the NASCET-defined threshold level of 50% or greater ICA stenosis, above which CEA results in stroke reduction. A management algorithm based on these criteria should help to minimize both angiography and unnecessary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The accuracy of quantification of stenoses less than 50% is generally poor, and clinical significance of mild narrowing is questionable in most cases. The North American Symptomatic Carotid Endarterectomy Trial [11]and Cina et al [12]concluded that symptomatic patients only benefit from surgery when their carotid artery is 50% or more stenosed. 29.6% (21 of 71) NPC patients in our study showed more than 50% carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of quantification of stenoses less than 50% is generally poor, and clinical significance of mild narrowing is questionable in most cases. The North American Symptomatic Carotid Endarterectomy Trial [11]and Cina et al [12]concluded that symptomatic patients only benefit from surgery when their carotid artery is 50% or more stenosed. 29.6% (21 of 71) NPC patients in our study showed more than 50% carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…121 This study measured stenosis using the ECST method, 72 whereas the other papers all used the NASCET method. 93,104,120 There were too few data in the ROC plot for 50-69% stenosis to say whether the points lay on a curve or not ( Figure 14). The results of testing for threshold effects using correlation coefficients are given in of 0-49% stenosis or occluded is very high, and this meta-analysis includes a possible outlier 93 ).…”
Section: Exploration Of Heterogeneitymentioning
confidence: 99%
“…13,14 We have followed the NASCET study and therefore defined stenosis of greater than 50% as significant stenosis. Conventional angiography is the gold standard accepted for grading of arterial stenosis.…”
Section: On 12 Patientsmentioning
confidence: 99%